2013
DOI: 10.1118/1.4790692
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative material characterization from multi‐energy photon counting CT

Abstract: Purpose:To quantify the concentration of soft-tissue components of water, fat, and calcium through the decomposition of the x-ray spectral signatures in multi-energy CT images. Methods: Decomposition of dual-energy and multi-energy x-ray data into basis materials can be performed in the projection domain, image domain, or during image reconstruction. In this work, the authors present methodology for the decomposition of multi-energy x-ray data in the image domain for the application of soft-tissue characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Other groups [25,63,64] have reported noisy regions with incorrect material identification of high-Z materials but they claimed their ability to detect low concentrations of high-Z materials with high accuracy by measuring the concentrations in decomposed images and comparing it to the true concentration value. Our results show that good correlation over the full range of the known and measured concentrations fails to provide information about the misidentification between different materials and the extent of such misidentification in decomposed material images.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups [25,63,64] have reported noisy regions with incorrect material identification of high-Z materials but they claimed their ability to detect low concentrations of high-Z materials with high accuracy by measuring the concentrations in decomposed images and comparing it to the true concentration value. Our results show that good correlation over the full range of the known and measured concentrations fails to provide information about the misidentification between different materials and the extent of such misidentification in decomposed material images.…”
Section: Discussionmentioning
confidence: 99%
“…They offer potential benefits in image quality and dose, arising from reduced electronics noise, capability for energy discrimination, and better use of low-energy photons (optimal energy weighting) compared to energy-integrating detectors (Tapiovaara and Wagner 1985, Tanguay et al 2013, Xu et al 2014). A variety of PCD-based x-ray systems have been proposed for applications such as mammography (Thunberg et al 2004, Fredenberg et al 2010a, Cole et al 2012), radiography (Francke et al 2001, Weigel et al 2014), tomography (Maidment et al 2005, Schmitzberger et al 2011, Alivov et al 2014), and energy-resolved imaging (Wang et al 2011, Alessio and MacDonald 2013, Silkwood et al 2013). A comprehensive review of current implementations, potential benefits, and clinical and preclinical applications of PCDs can be found in (Taguchi and Iwanczyk 2013).…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, DECT, such as dual-source CT, sometimes requires relatively high dose levels as compared to conventional CT, 11 and it is not safe for sequential studies. 12 As a result, these limitations currently exclude DECT from widespread use in several clinical applications and from serial studies in plaque imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that material decomposition with spectral CT imaging provides better differentiation of materials for atherosclerotic plaque features. 4,12,[28][29][30][31] Nonetheless, there are limited studies of quantitative metrics for evaluating performance in terms of objective image assessment exploiting a numerical observer in spectral CT imaging. 32 The major problems may be because it is difficult to correlate the data from different energy bins, especially given the complexity of the spectral CT data, since spectral CT imaging can be considered a four-dimensional (4-D) technique to form measurements in three spatial dimensions and a unique energy dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation